Truth and fake news in the classroom: the sense construction and the discoursive ethics in literacy practices - Santos de Lima, Antônio Carlos; Luz, Lilian Soares de Figueiredo; Correia, Aurineide Profírio Barros (Revista da ABRALIN, 2021)
This paper aims to present a proposal of literacy practice, which reflects current and relevant topics such as truth (FOUCAULT, 2014) and the fake news (FONTANA, 2021), from the perspective of discourse ethics (SOUTO MAIOR, 2020). In this proposal, we articulate the reflection on those topics together with the production of a review – a textual genre widely used in the academic sphere. We situate our proposal in the perspective of Applied Linguistics (AL), by focusing on the issue of language as a social practice, which reflects constitutive aspects of society and culture that is crossed by discursive practices built from ideological threads (FABRÍCIO, 2006) and, for this reason, are present in literacy practices. In this proposal we have used the movie called "The invention of lying" (2009), because we could realize this movie as a useful resource that allow subjects to reflect about different aspects which they face in their social context and is related to writing and reading process in the world (LIMA; SOUTO MAIOR, 2020)